Market discipline in life insurance: Does public risk disclosure encourage less risky management actions? - Moritz Hanika (Journal of Risk and Insurance, 2025)
We analyze how public risk disclosure, specifically Solvency II, impacts life insurers' risk-taking behavior. Using data from 58 German life insurers from 2016 to 2023, we find that publicly reported solvency ratios can affect premium growth and surrender rates. Moreover, insurers appear to improve their solvency ratios following a decline in the previous year. To investigate whether policyholder behavior drives a life insurer's reduced risk-taking, we then develop a model in which a life insurer seeks to maximize shareholder value. Unlike previous research, we consider annually disclosed solvency ratios, affecting policyholders' dynamic purchase and surrender behavior. In our model, the insurer acts less riskily (e.g., holds more reserves and sells less-risky insurance portfolios) to maintain higher solvency ratios and mitigate policyholders' adverse reactions. Our findings motivate public risk disclosure to strengthen market discipline, but its level and design must be carefully calibrated to be effective and avoid undue costs.
Keywords: 330; life insurance; market discipline; risk disclosure; shareholder value maximization